The Keris as a Medium of Communication: Ethnographic Insights into Elite Javanese Society and Social Dynamics - Muchammad Ismail; Ali Maksum; Riyanto; Siti Kholifah (Mediakita, 2026)
The keris serves as a profound symbol of identity and spirituality in the Indonesian archipelago. Beyond its function as a weapon, the keris carries high historical value and symbolic meaning, acting as a medium of cultural communication that expresses social status, spiritual beliefs, and moral legitimacy among the Javanese elite. Its existence sparks debate between ascetic perspectives, which reject its mystical elements, and cultural viewpoints, which regard ownership as a means of preserving Javanese tradition and spirituality. This research employs a qualitative ethnographic approach, collecting data through in-depth interviews, participatory observation, documentation, coding, thematization, and narrative analysis. The study uses Max Weber’s theory of social action as the interpretive framework to understand the symbolic role of the keris in elite Javanese society. The findings show that the Keris functions as a medium of symbolic communication linking rational, emotional, and traditional aspects within the social dynamics of the Javanese elite. Instrumental-rational action is reflected in the awareness of possessing and maintaining the keris as a strategy to reinforce social authority. Value-oriented action reflects moral and spiritual responsibility in the ritual care of the keris. Affective action manifests in emotional attachment and pride in the keris as a personal symbol. Finally, traditional action persists through inherited customs that sustain the continuity of keris culture.